Formation Of Public Policy in The Digital Era: Implications for Public Administration - Rika Kusdinar; Putra Pratama Wijaya (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
This study explores the dynamic of digital transformation in public service delivery, focusing on how technological advancements reshape public policy formulation. The objectives are to analyse the challenges and opportunities presented by the integration of digital technologies such as big data, artificial intelligent, and electronic based government system in fostering more inclusive, efficient, and responsive public services. Using a qualitative descriptive approach based on secondary data, the research examines the shift from a traditional bureaucratic model to a participatory and citizen-centred public service paradigm aligned with the principles of the new public services. The findings indicate that digital platforms empower citizens to engage in policy discourse, while big data analytics offer valuable insights into public needs and behaviours. However, this study highlights critical challenges, including privacy concerns, misinformation, and digital inequality. The implementation of SPBE demonstrates the potential for real-time, location-independent service delivery, yet requires adequate infrastructure and data governance frameworks. The research recommends that policymakers invest in robust digital ecosystems, enhancing data security, and promote digital literacy to maximize the benefits of transformation. Overall, the study concludes that digital innovation, if managed inclusively and ethically, can significantly enhance the effectiveness of public service and governance in the digital era.